Design DNA: theory reviewing behind the behavioral aspect in the levels of design / Izzuddinazwan Misri and Amer Shakir Zainol - Misri, Izzuddinazwan; Zainol, Amer Shakir (Faculty of Art and Design, 2021)
Behavioral was defined in various ways of perspective regarding lives such as humans, animals, and nature. Related to acting or behaving in general, the behavioral aspect in design is abbreviated to end in response, purposely to perceived stimulations that are linked to responses produced and the design that encourages the user to react. The design level was proposed and specified by Norman (2004) as the requirement, guideline, and characteristic aspects before design. This behavioral aspect is a vital component of design levels in every design that one desired to make. The function, usability, safety, operation, and user pleasure are the other definitions to the behavioral perspective in the design levels and, it is also the second level of design at consideration in designing things after the visceral level. As the design level is a fundamental subject in design, the theory reviewing here is exposing the formulation idea in the value for recognition, trade marking and identical aspects for product criteria specified in the behavioral level in adding product value called the 'design DNA'.